Development and validation of a LC‐MS/MS method for the in vitro analysis of 1‐hydroxymidazolam in human liver microsomes: application for determining CYP3A4 inhibition in complex matrix mixtures. (14th May 2013) - Mooiman, K. D.; Maas‐Bakker, R. F.; Rosing, H.; Beijnen, J. H.; Schellens, J. H. M.; Meijerman, I.
ABSTRACT: Complementary and alternative medicines (CAM) can affect the pharmacokinetics of anticancer drugs by interacting with the metabolizing enzyme cytochrome P450 (CYP) 3A4. To evaluate changes in the activity of CYP3A4 in patients, levels of 1‐hydroxymidazolam in plasma are often determined with liquid chromatography–quadrupole mass spectrometry (LC‐MS/MS). However, validated LC‐MS/MS methods to determine in vitro CYP3A4 inhibition in human liver microsomes are scarce and not optimized for evaluating CYP3A4 inhibition by CAM. The latter is necessary because CAM are often complex mixtures of numerous compounds that can interfere with the selective measurement of 1‐hydroxymidazolam. Therefore, the aim was to validate and optimize an LC‐MS/MS method for the adequate determination of CYP3A4 inhibition by CAM in human liver microsomes. After incubation of human liver microsomes with midazolam, liquid–liquid extraction with tert‐butyl methyl ether was applied and dried samples were reconstituted in 50% methanol. These samples were injected onto a reversed‐phase chromatography consisting of a Zorbax Extend‐C18 column (2.1 × 150 mm, 5.0 µm particle size), connected to a triple quadrupole mass spectrometer with electrospray ionization. The described LC‐MS/MS method was validated over linear range of 1.0–500 nm for 1‐hydroxymidazolam. The results revealed good inter‐assay accuracy (≥85% and ≤115%) and within‐day and between‐day precisions (coefficient of variation ≤ 4.43%). Furthermore, the applicability of this assay for the determination of CYP3A4 inhibition in complex matrix mixtures was successfully demonstrated in an in vitro experiment in which CYP3A4 inhibition by known CAM ( β ‐carotene, green tea, milk thistle and St. John's wort) was determined. Copyright © 2013 John Wiley & Sons, Ltd.